Minimal power manoeuvring techniques in nano-satellites - Lim, Noel Wei Shen (2016)
This study presents two unique ideas in manoeuvring nano-satellites. Both ideas make use of the theory of varying center of gravity to cause a change in moments and thus leading to rotation in nano-satellites. The center of gravity is varied by movement of a ball bearing in a system and it is automated with the help of SMAs. The first idea focuses on moving a ball bearing in a tube while the second idea is about moving a ball bearing on a wooden board. It is found that in theory, both ideas are feasible by calculating the angular velocity of the nano-satellites caused by a distance moved by the ball bearings. For the first design, a tube length and tilt angle of 10cm and 1.5⁰ respectively is able to spin a 20cm x 20cm x 20cm and 5kg nano-satellite by 1.5⁰/s with a force required of only 0.0131N. For the second design, a 6⁰ ramp angle & 2.389cm ramp length can spin a nano-satellite of the same dimensions and mass by 1.5⁰/s as well. The power required is also significantly smaller as compared to the current propulsion methods. Studies on a newly purchased air bearing system are also conducted and shown. Calibrations are done and its operating procedures are highlighted in this report to help future users understand its mechanism better. Due to the incompetence of the SMA, the designs are slightly modified. Experimental results on the air bearing’s linear stage show that the first idea works in reality but the second idea was largely ineffective. The linear stage moved about 10 – 18mm for design 1 whereas it only moved about 1mm for design 2. This is due to slight inaccuracies and inherent friction in the system. In all, the first idea is a promising one and more tests should be carried out to further prove its feasibility.